Traces of muscular fatigue in the rectus femoris identified with surface electromyography and wavelets on normal gait. - Fidalgo-Herrera, Alberto; Miangolarra-Page, Juan; Carratalá-Tejada, Maria (Physiotherapy Theory & Practice, 2022)
Background: Although the median frequency is used as a basis to assess the presence of muscular fatigue, some studies have found that it is not a good estimator for this purpose. Physiotherapists often deal with patients with movement issues related to fatigue. A new objective estimator that is easy to obtain and interpret can help with the management of such patients. Objective and Purpose: The aim of this study was to identify the frequency bands most affected by fatigue and propose a protocol to obtain such information. Methods: Thirty healthy subjects (age 22.05 ± 2.42 years, height 1.71 ± 0.08 m, and weight 68.75 ± 11.42 kg) were recruited to measure the rectus femoris electromyography (EMG) of both legs during gait, before and after a fatiguing protocol. Four frequency bands were studied: high frequency (107–250 Hz), midfrequency (65–94 Hz), 40 Hz (34–53 Hz), and low frequency (< 25 Hz). Each frequency band is related to different aspects of the muscular contraction. Results: The main finding is that the ratios of the 40-Hz frequency and low-frequency bands showed significant differences in both legs between pre-fatigue and post-fatigue recordings. Critical thresholds F* 4.86 and 4.93 were exceeded at 4.5–8.7%, 30.64–46%.38, 63.75–66.8%, and 83.69–90.79% and at 0–2.53%, 4.7–15.21%, 18.15–54.65%, and 55.81–99.95% of the gait cycle, respectively, with p values <.05. Conclusions: The low-frequency band constitutes the best indicator to assess fatigue in gait.